Pencegahan Stunting Berbasis Masyarakat dengan Pendampingan Posyandu dan Edukasi Gizi - Alfinatur Rosyidah; Dewi Ayu Fatimah; Nurul Khimah; Robiyatul Adawiyah; Nalim Nalim (JMIMAS: JURNAL PENGABDIAN DAN MITRA MASYARAKAT, 2026)
Stunting is a public health issue that significantly affects children’s physical and cognitive development. This study aims to evaluate the effectiveness of community-based stunting prevention through Posyandu assistance and nutrition education for mothers of toddlers in the study area. The methods employed involve routine interventions at Posyandu, including balanced nutrition education, growth monitoring, and the promotion of clean and healthy living behaviors delivered by local health cadres. The implementation activities consisted of child anthropometric measurements, direct counseling sessions, and group discussions designed to enhance mothers’ knowledge of childcare practices and the fulfillment of children’s nutritional needs. Data were analyzed by comparing children’s growth indicators before and after the intervention using descriptive and inferential statistical techniques. The findings reveal significant improvements in children’s weight and height, as well as increased maternal understanding of adequate nutrient intake and healthy practices. These results demonstrate that community-based interventions through Posyandu are effective in supporting stunting prevention by empowering mothers and families within their local environment. This study highlights the importance of strenghening the role of Posyandu and health cadres as the frontling of stunting prevention programs and emphasizes the need for continuous nutrition education to improve human resource quality from early childhood.